2019
DOI: 10.18502/kss.v3i11.4027
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance of Corporate Social Responsibility Disclosure on Public Companies in ASEAN Countries

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
(8 reference statements)
1
10
0
2
Order By: Relevance
“…CSR disclosures may increase transparency and reduce information asymmetry, which in turn would increase the credibility of the company in the market. This result was consistent with Agusti & Rahman, [11], Lako, [38] and Narullia et al, [31] who all found that corporate social responsibility disclosures had a significant impact on the value relevance of both net income and book value. A high level of CSR disclosure showed that a company was concerned about the impact of its operations on the surrounding economic, social, or environmental conditions.…”
Section: Hypothesis Testingsupporting
confidence: 91%
See 1 more Smart Citation
“…CSR disclosures may increase transparency and reduce information asymmetry, which in turn would increase the credibility of the company in the market. This result was consistent with Agusti & Rahman, [11], Lako, [38] and Narullia et al, [31] who all found that corporate social responsibility disclosures had a significant impact on the value relevance of both net income and book value. A high level of CSR disclosure showed that a company was concerned about the impact of its operations on the surrounding economic, social, or environmental conditions.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Agusti & Rahman [11] and Narullia et al, [31] found that CSR disclosures have an impact on the quality of the accounting information through the fluctuation of share prices following the issuance of the disclosures. In contrast, Schmelzer [28] found that CSR disclosures do not cause fluctuation in share prices.…”
Section: Image 1 Our Conceptual Framework Is Shownmentioning
confidence: 99%
“…Hal ini diakibatkan banyak dari investor yang sudah sadar bahwa pentingnya kepedulian perusahaan terhadap kondisi sosial dan lingkungan di sekitarnya. Namun di sisi lainnya menurut penelitian yang dilakukan oleh (Karuniawan & Nugrahanti, 2012;Narullia, Subekti, Azizah, & Purnamasari, 2019;Nuriyanto et al, 2020), pengungkapan tanggung jawab sosial tidak memiliki relevansi nilai sehingga tidak memberikan pengaruh apapun dan bahkan memberikan pengaruh negatif dalam pengambilan keputusan investor terhadap perusahaan. Hal ini bisa terjadi karena pada situasi tertentu, dimana salah satunya adalah ketika investor cenderung hanya melihat performa perusahaan yang bersifat keuangan saja.…”
Section: 2unclassified
“…Berdasarkan teori tersebut dapat dikatakan bahwa manusia akan mengumpulkan berbagai informasi untuk membuat keputusan investasi yang rasional dalam hal ini pelaporan keberlanjutan. Informasi yang relevan membuat investor dapat mengukur nilai perusahaan secara rasional (Narullia et al (2019); Narullia & Subroto (2018)).…”
Section: Pendahuluanunclassified